Training in Marketing Digital for UMKM Silverforr Int Community - Wicaksono, Kuspuji (SEEIJ (Social Economics and Ecology International Journal), 2023)
The development of technology has had a tremendous impact on the national economy, especially in the MSME sector. The main problem that must be faced by MSME players is that many of them do not keep up to date and are familiar with technological developments. Therefore, the government actively encourages MSME players in Indonesia to utilize it and expand market penetration into the digital realm. Online-based digital media is currently being use by MSME players because it can reach a wider market which requires relatively low capital. Digital marketing can be the alternative way in conducting marketing communications with customers for building transactions between MSMEs and consumers. This community service is being carried out by socialization, training in digital marketing operations, creating accounts and how to start selling them. The results of this community service are expected to contribute in improving the economy of MSME players, encourage them to be more open to technological developments and utilize them for adding value to these MSMEs.